2020
DOI: 10.21203/rs.2.21534/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nursing and midwifery students’ experiences and perception of their clinical learning environment in Malawi: A mixed method study

Abstract: Background The clinical learning environment is an important part of the nursing and midwifery training as it helps students to integrate theory into clinical practice. However, not all clinical learning environments foster positive learning. The aim of this study was to assess the experiences and perception of the clinical learning environment by nursing and midwifery students in Malawi.Methods A concurrent triangulation mixed methods research design was used to collect data from nursing and midwifery student… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…It also emerged from this study that despite the willingness of registered nurses to teach students, few patients are present in the wards, which may impede nursing students' practical application of theory. This finding links to a study by Mbakaya et al (2020), who found that having few patients in a ward hinders the clinical learning of nursing students.…”
Section: Theme 1: Participants' Understanding Of Clinical Teachingsupporting
confidence: 83%
“…It also emerged from this study that despite the willingness of registered nurses to teach students, few patients are present in the wards, which may impede nursing students' practical application of theory. This finding links to a study by Mbakaya et al (2020), who found that having few patients in a ward hinders the clinical learning of nursing students.…”
Section: Theme 1: Participants' Understanding Of Clinical Teachingsupporting
confidence: 83%
“…When the clinical environment is well resourced it supports the students in the acquisition of skills (Haraldseid et al, 2015; Mbakaya et al, 2020). In Ghana, students have reported that the equipment in the clinical placement area allows them to learn skills (Atakro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%